Dynamic Impact of Work Satisfaction and Organizational Commitment - Agarwal, Kirti; Ranjan, Shiv (Journal of Commerce and Trade, 2010)
High performance of the lecturers in the majority of Private institution in North India still something beyond reachable. The increasing capability to manage and to develop the higher education institution has become more and more important, including the usage of modern managerial principles possessing high quality. In the point of view of the owner and provider of the higher education institution, quality management system basically contains continuous improvement for the system concerned . This article tries to dissect the underlying problems that hinder the target. To solve this problem, as a researcher conducted a research among the lecturers form the private colleges in north India. The method used in this research is survey method, namely descriptive survey and explanatory survey. We surveyed 30 private colleges in north India. The research results proves that job satisfaction, organizational commitment and turnover intention both simultaneously and partially have a significant influence on the performance.